2012
DOI: 10.1007/978-3-642-28951-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Nonmultiplying Bacteria are Profoundly Tolerant to Antibiotics

Abstract: Bacteria survive treatments with antimicrobial agents; they achieve this in two ways. Firstly, bacteria quickly become tolerant to these agents. This tolerance is temporary, reversible, and associated with slowing of the multiplication rate. Secondly, bacteria can undergo genetic mutations leading to permanent clonal resistance to antimicrobial agents. In patients with infections, nonmultiplying bacteria, some of which may be viable but nonculturable, exist side by side with multiplying bacteria. Current antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 144 publications
0
27
0
Order By: Relevance
“…Experiments were further focused on stationary-phase cultures, since the absence of active growth, a higher persister fraction, and nutritional starvation result in a more pronounced antibiotic tolerance and, partly due to the similarities to biofilms, increased clinical relevance (13,41). Other antipersister molecules primarily aimed at targeting nonmultiplying cells have been described for Mycobacterium tuberculosis (42) and S. aureus (43).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were further focused on stationary-phase cultures, since the absence of active growth, a higher persister fraction, and nutritional starvation result in a more pronounced antibiotic tolerance and, partly due to the similarities to biofilms, increased clinical relevance (13,41). Other antipersister molecules primarily aimed at targeting nonmultiplying cells have been described for Mycobacterium tuberculosis (42) and S. aureus (43).…”
Section: Discussionmentioning
confidence: 99%
“…During food pasteurization and preservation processes, certain bacterial cells can be induced to enter the VBNC state (Zhao F. et al, 2013; Kramer and Muranyi, 2014). In general, VBNC cells are resistant to multiple antimicrobials, which may cause treatment failure at times (Hu and Coates, 2012). In fact, a recent study found that foods subjected to antimicrobial treatment harbored considerable numbers of VBNC cells (Anvarian et al, 2016).…”
Section: Characteristics Of Vbnc Cellsmentioning
confidence: 99%
“…During the process of infection and in the course of treatment regimens, certain bacterial cells can transfer into the VBNC state. In this state, the bacteria are generally resistant to multiple antimicrobials and this may cause treatment failure at times (82). A good example of this phenomenon is the drug resistance of tuberculosis.…”
Section: Effects Of Antimicrobialsmentioning
confidence: 99%
“…A good example of this phenomenon is the drug resistance of tuberculosis. The non-culturable Mycobacterium tuberculosis is multi-drug resistance and may prolong the infection and chemotherapy for long time (82). …”
Section: Effects Of Antimicrobialsmentioning
confidence: 99%